Each of us a desert - Oshiro, Mark (Tom Doherty Associates, 2020)
Xochitl is destined to wander the desert alone, speaking her troubled village's stories into its arid winds. Her only companions are the blessed stars above and enigmatic lines of poetry magically strewn across dusty dunes. Her one desire is to share her heart with a kindred spirit. One night, Xo's wish is granted, in the form of Emilia, the cold and beautiful daughter of the town's murderous conqueror. But when the two set out on a magical journey across the desert, they find their hearts could be a match, if only they can survive the nightmare-like terrors that arise when the sun goes down.